Analysis of Generation Z Communication Identity in Novo Club Online Community Members - Angelia Revina; Haris Annisari Indah Nur Rochimah (Publikasi Indonesia, 2024)
Generation z in Indonesia has a high interest in joining online communities or groups. Through online communities, Generation Z can interact via digital media or directly with people who have similar interests. So, it will be easier for them to show their identity. However, there are several irresponsible parties who take advantage of Generation Z's enthusiasm by exploiting their creative ideas. In this way, there is a potential that the identity that one wants to show and develop cannot be achieved. Therefore, it is important for a community to support generation z in forming the identity that its members want. This research aims to analyze the communication identity of Generation Z who are members of the Novo Club online community. The research method used is a qualitative approach using interviews and observation as data collection methods. The research results show that the communication identity that Novo Club members want to show is very diverse, including being an innovator, and in accordance with the positive characteristics of Generation Z. They show their identity through social media or in person, through their style of speaking and dressing.